2008
DOI: 10.1016/j.aap.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The experiences and perceptions of heavy vehicle drivers and train drivers of dangers at railway level crossings

Abstract: Heavy vehicle-train collisions have the potential to be catastrophic in terms of fatalities, environmental disaster, delays in the rail network, and extensive damage to property. Heavy vehicles, such as 'Road Trains' and 'B-Doubles', are vulnerable road users due to their size and mass and require specific risk management solutions. The present study aimed to capture the experiences of heavy vehicle drivers and train drivers at road-rail level crossings, with a view to exploring the contributing factors toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…It has yet to be confirmed whether pedestrians make calculated risks, although it has been hypothesised that some weigh the perceived safety of a route against the time and effort that would be required to use it (Lobb, 2006). Additionally, researchers have suggested that risky crossing behaviour may be reinforced if individuals consistently engage in such behaviour and avoid the negative consequences (Cooperative Research Centre (CRC) for Rail Innovation, 2010; Davey et al, 2008). This phenomenon is otherwise known as "punishment avoidance."…”
Section: Errors Versus Deliberate Violationsmentioning
confidence: 96%
“…It has yet to be confirmed whether pedestrians make calculated risks, although it has been hypothesised that some weigh the perceived safety of a route against the time and effort that would be required to use it (Lobb, 2006). Additionally, researchers have suggested that risky crossing behaviour may be reinforced if individuals consistently engage in such behaviour and avoid the negative consequences (Cooperative Research Centre (CRC) for Rail Innovation, 2010; Davey et al, 2008). This phenomenon is otherwise known as "punishment avoidance."…”
Section: Errors Versus Deliberate Violationsmentioning
confidence: 96%
“…Dengan kondisi lalu lintas yang semrawut, pengguna jalan menjadi tidak sabar, khususnya saat mereka terhalang pintu LC saat harus menunggu KA yang lewat dalam waktu yang tidak menentu (Leibowitz, 1985). Dan, pengguna jalan yang tidak sabar dan ceroboh cenderung meningkatkan kecepatan kendaraannya untuk mendahului KA melintas pada LC tersebut (Davey et al, 2008). Ketika pengguna jalan mendekat kearah LC, probabilitas kegagalan pengguna jalan dalam mengurangi kecepatan kendaraan sebesar 0.308 sedangkan probabilitas kegagalan pengguna jalan dalam memperhatikan rambu-rambu dan sinyal adalah 0.046 (Findiastuti, Wignjosoebroto dan Dewi, 2010).…”
Section: Perilaku Pengguna Jalanunclassified
“…According to the investigation of the Office of the Chief Investigator (OCI), the truck driver in this study was not aware of the train and the activated state of the LX until it was too late to stop. A study conducted by Davey et al (2008) discussed the intentional violation of vehicle drivers crossing LXs, particularly focusing on vehicle driver complacency due to the high level of familiarity. Tey et al (2011) conducted an experiment to measure vehicle driver response to LXs equipped with stop signs (passive), flashing lights and half barriers with flashing lights (active) respectively.…”
Section: Literature Review On Level Crossing Safety Studymentioning
confidence: 99%